Analysis of the effects of eating and emotions on reproductive axis function in patients with functional hypothalamic amenorrhea - Ye Lu; Yao Chen; Yuting Zhao; Yulu Wang; Hang Chen; Feifei Zhang; Xin Li (Taylor & Francis Group, 2024)
Objective: To investigate the effects of eating and emotions on reproductive axis function in patients with functional hypothalamic amenorrhea (FHA).Methods: A retrospective cohort study was conducted to summarize the clinical and endocrine characteristics of 58 patients with FHA at initial diagnosis and to follow up the recovery of ovulation and spontaneous menstruation in the patients to investigate these biochemical indicators and their effects on recovery outcomes.Results: Among patients with FHA, 13.8% (8/58) and 15.5% (9/58) had above moderately severe depressive and severe anxiety symptoms respectively, and 25.9% (15/58) were at high risk for eating disorders. 34.5% (20/58) were included assessed as having recovered. The non-recovered group had higher scores on the Patient Health Questionnaire (PHQ-9) (p = .022) and higher scores on the Eating Attitude Test-26 (EAT-26) (p = .03) as well as bulimia and food preoccupation (p = .041). Follicle diameter >5 mm at initial diagnosis was an independent factor influencing recovery of reproductive axis function (odds ratio = 7.532; 95% confidence interval, 1.321-42.930; p = .023).Conculsions: Mood disorders and a certain risk of eating disorders were present in FHA.These, together with weight loss, endocrine and follicle size, could influence the outcome.